First record of a new Sarcocystis species isolated by genetic analysis from beef meat in Baqubah, Iraq - Abood, E. N.; Al-Zubaidei, H. H. H. (Scientific Progress & Innovations, 2025)
Sarcocystosis is important disease in Asia, especially the western regions of the continent. It is considered one of the important zoonotic diseases, the infection wide geographic spreading caused by various species. in Iraq the disease is cosmopolitan infected man and animals leading to public health disorders and economic losses in meat production. the study was made to demonstrate the Sarcocystis species from local beef meat in Diyala provinces. Sarcocysts isolated from esophagus of 100 cattle were slaughtered at Diyala slaughter house during the period from November 2023 to May 2024. Cattle age ranged from 2–5 years. Different traditional techniques was made to detected sarcocystosis, peptic digestion technique were high sensitive technique 100 % methods. Then Trichnoscopy were (30 %) while the squeezing less sensitive (26 %) respectively. The majority of male animals recorded higher infection incidence 75 % while the females cattle rate was 53.8 % from the total exanimated animals. The result showed that the highest infection rate were recorded in animal of old age above 4 year old 100 % with significant differences between the age groups. The bradyzoites of Sarcocystis parasite were seen by examining the sediment of the digested muscle fluid as banana shape with a spik end of front and rounded rear end and slightly clear nucleus positioned toward the rear end,measurements 13.2 × 2.8 μm. The study was depending on using a traditional thermocycler PCR, as well as Sequencing, genotyping analysis of the Sarcocystis isolated from Diyala (Baqubah), Iraq. Extracted and isolate of genomic DNA of Sarcocystis, depending on Gene aid, obtained from Tissue cells extraction by using peptic digestion technique according to manufacturer protocol. Primer amplified using fragment over 900 bp. The purity of DNA was demonstrated by Nanodrop spectrophotometer at range (1.6–1.8 ng/μL), Sarcocystis levinei was detected for the first time in Iraq. The genetic analysis showed that the Iraqi isolates of Sarcocystis cruzi given a remarkable homology (100 %) with Norway, China, Iran, Turkey, India, Japan and Argentina respectively.